Impact of CYP3A4 single nucleotide polymorphism to lidocaine therapy in Pakistani population - Afzal, Ayesha; Uzma Naeem; Abeera Sikandar; Saima Rafique; Akbar Waheed Syed (Journal of the Pakistan Medical Association, 2025)
Objectives: To evaluate the role of the Cytochrome P450 3A4*22 mutation on the postoperative analgesic effects of lidocaine. Method: The study was conducted at the Pakistan Ordinance Factories Hospital, Wah Cantt, Pakistan, from March 2021 to December 2022, and comprised adult patients undergoing elective laparoscopic cholecystectomy. The patients were randomised into intervention group A and control group B. Patients in group A were given a bolus dose of lidocaine 2mg/kg in addition to the standard anaesthesia protocol, while The patients in group B received the standard anesthesia protocol. Visual analog scale was used at 6 hours and 12 hours post-surgery. Blood samples for genetic analysis were taken after the start of surgery. Data was analysed using SPSS 26. Results: Of the 300 patients, 215(71.7%) were females and 85(28.3%) were males. The overall mean age was 48.49±11.34 years and mean body mass index was 23.40±7.0546kg/m2. However, owing to unsuccessful genotyping, 42(14%) patients could not be evaluated. Patients with a GA allele sequence with GG in the Cytochrome P450 3A4*22 (rs35599367) had a higher postoperative pain threshold than those with GG and AA alleles alone (p<0.01). Conclusion: Patients with a GA allele succession with GG in the Cytochrome P450 3A4*22 (rs35599367) had a higher postoperative aggravation edge than those with GG and AA alleles alone. RCT No: IRCT-20220830059302N1. Keywords: Pharmacogenomics, Pharmacogenetics, Pain, Anesthesiology, Polymorphism, Genetics.